What it takes: scaling Impact-Linked Finance implementation capacity - Rutsch, Janine (Graduate School of Business (GSB), 2025)
Impact-Linked Finance (ILF), a range of financial solutions for market-based organisations that link financial rewards to social outcomes, has emerged from the evolving field of outcomes funding to support impact enterprises in pursuing high-quality impact while scaling toward commercial viability. The benefits of ILF are directed toward impact enterprises and outcome payers, who effectively pay only for impact created. However, broader adoption by transaction managers is necessary to scale implementation capacity and make the solutions accessible for impact enterprises. This study explored the factors influencing adoption of ILF by transaction managers, addressing two primary research questions: the limiting factors preventing the adoption of ILF and the enabling factors that facilitate its use. A qualitative approach was taken by conducting a comprehensive review of existing literature, interviewing twenty transaction managers about their respective experiences and perceptions, spanning impact investors, grantmakers, non-profit organisations and advisors, and conducting a thematic analysis of the data collected. The findings from the thematic analysis identified that for transaction managers for which ILF is a relevant strategy, key enabling factors include the availability of concessional and flexible funding to test and develop an ILF implementation approach; whether transaction managers are oriented towards innovative finance; and that a transaction manager is willing and able to prioritise impact goals in their investing activities. Conversely, eleven significant barriers limit ILF adoption. A predominant challenge is the lack of awareness of ILF, given its niche status and limited track record. This is exacerbated by a scarcity of experts with the necessary skills for high-quality ILF implementation, creating a bottleneck for supporting new adopters. Further, the complexity of ILF, including the balancing of diverse stakeholder interests, legal challenges, and the intricacies of structuring transactions, poses considerable difficulties. Particularly, transaction managers face challenges when target investees struggle to meet ILF's rigorous impact data requirements, often accompanied by high transaction costs. The study concludes that overcoming these barriers requires targeted interventions and market-building efforts to bolster ILF adoption. The research underscores the need for a concerted effort to increase awareness, build capacity, and streamline processes to leverage ILF's full potential in achieving the UN Sustainable Development Goals.